The service-productivity learning cockpit: A business intelligence tool for service enterprises - Sebastian Walther; Gaurang Phadke; Torsten Eymann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2012)
The paper describes the development of an agent-based simulation tool for hospital managers to manage their productivity of services, especially in the context of supporting services like patient transport logistics. The learning cockpit allows hospital managers to see how the change of inputs changes the overall perceived customer values of all stakeholders and therefore to get a visualization of the impacts their decisions cause. The paper introduces the general research domain service-productivity, followed by a description of the development steps of artefact creation. The learning cockpit is part of a research project called BELOUGA, which is funded by the German government.
urn:nbn:de:bvb:703-opus4-9576
Keywords: 650